Ant Colony Optimization in Thinned Array Synthesis With Minimum Sidelobe Level - Quevedo-Teruel, O.; Rajo-Iglesias, E. (IEEE antennas and wireless propagation letters, 2006)
The synthesis of unequally spaced large arrays is computationally unapproachable without using an optimization technique. In complex structures, gradient implementations converge to local minima and cannot be used to obtain a desired solution. Thus, global search methods are necessary to get specific design characteristics. In this letter, we propose the ant colony optimization (ACO) as an useful alternative in the thinned array design, using the sidelobe level (SLL) as the desirability parameter. Some examples have been proposed and solved to demonstrate the functionality of this technique for both linear and planar arrays